The Effect of Motivation on Memory Recall Among the Students of SS 11A and SS 11B of Government Model Secondary School Makurdi - Zakariah, Danladi; Ihaji, Elvis O.; Akafa, Tensaba Andes; Oladele, Gloria Omonefe; Iseko, Kingsley Iyoko; Akafa, Vika Tensaba; David, Izam Emmanuel; Ujah, Oche Williams (Darul Yasin Al Sys, 2024)
This study investigated the effect of motivation on memory recall among students of SS11A and SS11B of Government Model Secondary School Makurdi. The study employed the use of experimental design of 3x2x1 One-Way Analysis of Variance (ANOVA) and Independent T test with Alpha level of .05 to test the two hypotheses. The study consists of sixty (60) participants with 30 (50%) males and 30 (50%) females. Their ages ranged from 13-20 years with the means of 8.15 (SD=23.41). The participants were grouped into three of high, low and non-motivated students. Each group had (20) participants each totalling sixty (60) in the study. The participants were selected on the basis of gender and evenly distributed through the use of purposive and convenience sampling techniques. Finding from the study indicated that there was significant different in the level of memory recall among the high, low and non-motivated students F (2, 57) =8.98, P<.05. There was no significant different between male and female students on memory recall when motivated (59) =.20 P>.05. Thus, the first hypothesis was confirmed and the null hypothesis was rejected. On the other hand the second hypothesis was rejected and the null hypothesis was accepted. It was therefore recommended that conscious efforts should be made by the parents, Teachers, School Administrators to provide various incentives to enhance students recall abilities in memory task. It was also recommended that the Government and Philanthropists should provide scholarship programme to enhance study memory recall in the Secondary School. Finally, the study recommended that psychologists and the teachers should encourage the student to always rehearse their work in order to improve their memory recall when the need arise.